Form and Type of Code Mixing among Arabic language and Indonesian language - Humaidi Humaidi (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2020)
Social linguistics is the science that benefits our lives. One of the benefits of social linguistics is choosing the best languages ​​when we want to speak. Language has the norm in conversation when we communicate with the other person, for example, if we talk with a son or daughter, we must use good words when speak with our parents, and in contrasts when we talk with our friend, so we has used generic words without thinking about the ethics of speaking. In this case, everyone has to choose the language with a best and most beneficial language. There are three types of popular language choice in social linguistics, It is the code transformation, code mixing, and a method in the same language. In this research, the focuses on the study is form and type of code mixing among students of the Department Arabic Language Teaching, because code mixing has happened a lot to students on the other. The aim of this research is to know the forms and types of code mixing. This research used qualitative method, with three method of date collecting – observation, interview and collect date, and the basic of observation is the hearing and writing (sima 'catat) about the aspects of languages. Conclusion - Forms of code mixing that happened to university students, in Department of Language Teaching STAI Syaichona Moh. Cholil, is focuses on two forms, namely code maxing of words, for example Afwan saya datang terlambat ustadz . And the Vocabulary code maxing, for example hidupkan mirwahah. As for the types of code mixing that happened to university students, in Department of Language Teaching STAI Syaichona Moh. Cholil, is also focused on mixing the external code and does not happen much about mixing the internal code.